Impact of marketing to improve patient access to care and clinic utilization for clinical pharmacy specialists - Nora Bairagdar, PharmD, BCPS; Ashley Reich, PharmD, BCPS, BCPP; Jessica Bovio Franck, PharmD, BCPS (American Association of Psychiatric Pharmacists, 2023)
Introduction: This quality improvement initiative aimed to implement a strategy to increase access to care with clinical pharmacy specialists (CPSs), optimize CPS direct patient care activities, and promote clinical pharmacy services. The primary objective was to assess the impact of patient marketing on expanding access to care and clinic utilization in a CPS clinic. Methods: A marketing technique was applied by a mental health (MH) CPS to expand clinical pharmacy services. Direct-to-patient brochures advertising MH CPS comprehensive medication management services were placed at the check-in window of an interdisciplinary outpatient MH clinic. Brochure content included a description of an MH team, the role of MH CPSs, and benefits of being managed by MH CPSs. Patients could contact the MH CPS or speak to their primary provider for referral. The preintervention and postintervention evaluation periods were 4-month time frames. Clinic utilization for the MH CPS clinic was compared before and after dissemination of marketing brochures. Additional outcomes evaluated were number of encounters, number of patients seen, and number of clinical interventions completed by the MH CPS. Results: There was a significant increase in clinic utilization postintervention. The total number of encounters, patients, and clinical interventions were numerically increased postintervention. Discussion: The observed improvements in clinic utilization suggest the benefit of marketing in optimization of access to care in CPS clinics and justification of clinical pharmacy services.